The politics of cultural capital: Social hierarchy and organizational architecture in the multinational corporation - Levy, Orly; Reiche, B. Sebastian (SAGE, 2017)
How is social hierarchy in multinational corporations (MNCs) culturally produced, contested and reproduced? Although the international business literature has acknowledged the importance of culture, it gives little consideration to its role in constructing social hierarchies and symbolic boundaries between individuals and groups within MNCs. We take a Bourdieusian approach to understanding the role of cultural capital in structuring the social hierarchy in the MNC under two contrasting organizational architectures: hierarchical and network architecture. We argue that cultural capital serves as an instrument of power and status within the MNC, influencing access to valuable resources such as jobs, rewards and opportunities. Our framework further suggests that the transition from hierarchical towards network architecture sets in motion a high-stakes political struggle between headquarters and subsidiary actors over the relative value of their cultural capital in a bid to preserve or gain dominance and to determine the ‘rules of the game’ that order the social hierarchy in the MNC. We elaborate on this political struggle by theorizing about the relative dominance of cultural versus social capital, the content and relative value of firm-specific and cosmopolitan cultural capital, and the convertibility of cultural capital into other forms of capital under hierarchical and network architectures.
Keywords: Bourdieu; cultural capital MNC; multinational corporation; organizational architecture; social capital; social hierarchy